Strained germanium for applications in spintronics. Issue 11 (2nd November 2016) - Morrison, Christopher; Myronov, Maksym
Abstract : Germanium (Ge) is another group‐IV semiconductor material, which recently started attracting tremendous attention in spintronics following success of silicon (Si). The crystal inversion symmetry of Si and Ge precludes the spin relaxation of conduction electrons by the Dyakonov–Perel mechanism, resulting in a long spin relaxation time. Since the proposal of the spin FET in 1990 by Datta and Das, semiconductor materials have been studied for their spin–orbit (S–O) interactions, particularly those that can be modified by an applied electric field, such as the Rashba S–O interaction, in order to create devices that utilise spin modulation and control to perform logic operations. Since then new proposals have appeared. Nowadays they include spin transistors with several different operating principles, spin‐based diodes, spin‐based field programmable gate arrays, dynamic spin‐logic circuits, spin‐only logic, spin communication and others. In this review, the focus will be made on presenting recent progress in Ge spintronics including the key advances made. The absence of Dresselhaus S–O coupling in Ge enables a longer spin diffusion length when compared to III–V semiconductor materials. Evidence of a strong Rashba S–O interaction in strained Ge quantum wells has begun to emerge. Also, the first experimental demonstration of room‐temperature spin transport in Ge has recently been reported. Abstract : In this review, the focus is made on presenting recent progress in Ge spintronics including the key advances made. The absence of Dresselhaus spin‐orbit (S–O) coupling in Ge enables a longer spin diffusion length when compared to III–V semiconductor materials. Evidence of a strong Rashba S–O interaction in strained Ge quantum wells has begun to emerge.